A Contourlet-Based Image Watermarking Scheme with High Resistance to Removal and Geometrical Attacks. (27th June 2010) - Khalighi Khalighi, Sirvan Sirvan; Tirdad Tirdad, Parisa Parisa; Rabiee Rabiee, Hamid R. Hamid R.
Abstract : We propose a new nonblind multiresolution watermarking method for still images based on the contourlet transform (CT). In our approach, the watermark is a grayscale image which is embedded into the highest frequency subband of the host image in its contourlet domain. We demonstrate that in comparison to other methods, this method enables us to embed more amounts of data into the directional subbands of the host image without degrading its perceptibility. The experimental results show robustness against several common watermarking attacks such as compression, adding noise, filtering, and geometrical transformations. Since the proposed approach can embed considerable payload, while providing good perceptual transparency and resistance to many attacks, it is a suitable algorithm for fingerprinting applications.